CARVING SKIS - A BENEFIT OR A TREND? - Aleksandar Joksimović; Danilo Aćimović; Omer Špirtović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The introduction of innovations in sport often is met with opposition from society, or in other words, incomprehension from the supporters of previous premises, in terms of understanding the new methods and the like. The manifestation of a certain dose of resistance is most frequently done by voicing unsubstantiated criticism by means of the media. We are primarily referring to the incomprehension of new methods and principles of work, which leads to prejudice among poorly or insufficiently informed individuals. This was the reason why, at first, during the 1990's, a prejudice against carving skis was born, which could confuse the inexperienced and uninformed, and should therefore be clarified. Carving is much easier to learn than classic skiing. There is pleasure to be gained from the very fact that carving skis, due to their structure, have no problem entering and going through a turn, the ease of which can be seen in the relaxed body posture during that time. The term "carving" refers to the shape of the skis, which remind one of an hourglass shape. Depending on how far the tip and tail of the skis are from the mid section of the skills, we can determine various carving ski types, from the mildest to the most extreme, including: carving plus skis, all-round carving skis, classic skis, turn skiing, telemark - free skiing.